TO SEEK ONE’S FORTUNE: LABOUR MIGRANTS FROM THE WESTERN BALKANS IN NORWEGIAN HOSPITALITY INDUSTRY - Kalenjuk, Bojana M; Đerčan, Bojan; Tešanović, Dragan; Lukić, Tamara; Banjac, Maja (Turizam, 2020)
The hospitality industry is known for the large fluctuation of labour. The subject of this study is hospitality workers from the countries of the Western Balkans. The task was to investigate the reasons for their coming to the northern regions, as well as the experience and knowledge gained while working in their restaurant facilities. The aim of the paper was to obtain information on the reasons for the selection of these sites, differences in work and experiences, as well as future plans. The results showed that there is considerable satisfaction with the work in the Scandinavian countries. The key item in easy adjustment and destination selection is played by living standards i.e. income, which is the focus of the interest of migrant workers from the Western Balkan countries.
Keywords: Labour migration; restaurant; catering; South-eastern Europe; Western Balkans